PENGARUH INFORMASI AKUNTANSI TERHADAP RETURN SAHAM (Studi pada Perusahaan LQ-45 di Bursa Efek Jakarta) - Norsain Norsain; Dina Kurniawati (Fakultas Ekonomi dan Bisnis, 2018)
The use of financial information through financial statements as a result of anaccounting process in a company is important information in analyzing the long-terminvestment returns. Through this analysis, investors will be able to assess the company'sprofitability, quality of management performance, and prospects of the company. Thetype of data used in this study is panel data, which is a combination of cross section andtime series, financial report data of 45 companies that become the research sample forthe period 2010 to 2013. The data sources used in this study are secondary data, namelydata in the form of documents and information related to the object of research publishedby the Indonesia Stock Exchange through the authority of the Capital Market InformationCenter accessed from the official website of the IDX After the data is collected, the data isanalyzed using the EVIEWS program for the panel data type. Beginning with the analysisof model selection, then proceed with the classical assumption test. Research resultsVariable X1 Price Earning Ratio (PER), has no effect on variable Y (stock return),Variable X2 Price to Book Value (PBV) is having a significant impact on variable Y(stock return), Variable X3 Return on Assets (ROA) has a significant effect on variable Y(stock return). Simultaneously the variables PER, PBV, ROA have a significant impact onthe level of α = 10%